Evaluasi yang Tepat terhadap Kebutuhan Peserta Didik pada Pembelajaran PAI - Muhammad Hasbullah (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
This study explores the challenges in evaluating student needs within Islamic Religious Education (PAI), where current evaluation practices remain poorly structured and insufficient to fully address student needs. The study aims to improve the effectiveness of PAI education by developing more accurate assessments of teacher roles, preparation, and the learning process. Through a qualitative approach and literature review methodology, this research analyzes relevant academic sources to identify gaps in current evaluation practices and potential solutions for enhancing PAI learning. Key findings reveal that a targeted and comprehensive evaluation framework not only helps meet students' educational needs but also fosters their motivation and sincerity in learning. The implications suggest that a more structured evaluation system can enhance teaching effectiveness and student engagement in Islamic education. Moreover, environmental factors, including school support and parental roles, are recognized as critical in addressing students' learning needs. Therefore, a comprehensive and focused evaluation approach is expected to offer effective solutions for advancing the PAI education system in the future.